2013
DOI: 10.4028/www.scientific.net/amr.706-708.197
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties and Antibacterial Activity of a Chitosan Film Incorporated with Lavender Essential Oil

Abstract: Chitosan-based films containing lavender essential oil (LEO) (0, 0.5%, 1.0%, 1.5% (v/v)) were prepared to evaluate their physical and antibacterial activities. In order to study the impact of the incorporation of LEO into chitosan matrix, the solubility, mechanical property, water vapor permeability, and antibacterial activity of the films were investigated. Fourier transform infrared chromatography (FTIR) was carried out to explain structure–property relationships. Results showed that the solubility and water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…As reported by Souza et al [133], the resistance to the water vapor diffusion of chitosan films could be increased by adding the carp oil. On the other hand, Zhang et al [134] indicated that chitosan films containing lavender oil exhibited lower water vapor permeability. The decreasing moisture sorption of chitosan coating film was observed with increasing concentration of olive oils [132].…”
Section: Physical Property Of Chitosan-based Coating With Antimicrobimentioning
confidence: 99%
“…As reported by Souza et al [133], the resistance to the water vapor diffusion of chitosan films could be increased by adding the carp oil. On the other hand, Zhang et al [134] indicated that chitosan films containing lavender oil exhibited lower water vapor permeability. The decreasing moisture sorption of chitosan coating film was observed with increasing concentration of olive oils [132].…”
Section: Physical Property Of Chitosan-based Coating With Antimicrobimentioning
confidence: 99%
“…Lavender stands as one of the world's most frequently utilized aromatic plants, with its extracts and essential oils having a longstanding tradition of being employed to address conditions like epilepsy and migraines. Lavender inspired and propelled the cosmetics industry and, more recently, the food supplements industry [53,54]. Inspired by the healing properties of lavender, known and successfully exploited in the past centuries, researchers are currently studying the expansion of the fields of use, such as in dentistry and surgery.…”
Section: Introductionmentioning
confidence: 99%